Management of a Facilitated Aesthetic Orthodontic Treatment with Clear Aligners and Minimally Invasive Corticotomy - Silvia Caruso; Atanaz Darvizeh; Stefano Zema; Roberto Gatto; Alessandro Nota (Dentistry Journal, 2020)
Accelerating orthodontic tooth movement has become a topical issue and the corticotomy seems to be the only effective and safe technique reported in the literature. Simultaneously, aesthetic orthodontic treatment with removable clear aligners has become commonly requested. The aim of this paper is to illustrate the management of facilitated aesthetic orthodontic treatment, a combined approach including piezocision corticotomy and clear aligners for orthodontic treatment. Orthodontic planning for traditional clear aligners should be modified to take advantage of the corticotomy technique in order to facilitate the most difficult orthodontic movements needed to achieve treatment completion, where each aligner will be used for four days rather than 15 days for a total time of four months. A corticotomy with a modified minimally invasive flapless piezocision technique should be performed in both jaws at the same time, before the time window of the orthodontic treatment, where the most difficult orthodontic movements are planned. Treatment planning where difficult orthodontic movements, such as anterior open-bite closure and extraction space closure, are easily managed with clear aligners and are presented as examples of facilitated aesthetic orthodontic treatment application. The combination between aesthetic treatment with clear aligners and modified piezocision corticotomy, if carefully planned, seems to represent a synergy that achieves the current goals of orthodontic treatment. The primary objectives of this combination should be facilitating difficult orthodontic movements and reducing treatment duration.